2022
DOI: 10.3390/rs14030740
|View full text |Cite|
|
Sign up to set email alerts
|

The Brazilian Soil Spectral Service (BraSpecS): A User-Friendly System for Global Soil Spectra Communication

Abstract: Although many Soil Spectral Libraries (SSLs) have been created globally, these libraries still have not been operationalized for end-users. To address this limitation, this study created an online Brazilian Soil Spectral Service (BraSpecS). The system was based on the Brazilian Soil Spectral Library (BSSL) with samples collected in the Visible–Near–Short-wave infrared (vis–NIR–SWIR) and Mid-infrared (MIR) ranges. The interactive platform allows users to find spectra, act as custodians of the data, and estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
1
8
0
Order By: Relevance
“…As regional and global efforts to share large spectral libraries and build spectroscopy‐based estimation services are increasing (Demattê et al., 2022; Shepherd et al., 2022), it is critical to understand when calibration transfer is necessary. Harmonizing spectral collection to be consistent with the primary instrument may avoid the need for calibration transfer but given the diversity in instrument types and set‐ups (Benedetti & van Egmond, 2021), it is likely that the need for calibration transfer will at least have to be tested on a case‐by‐case basis.…”
Section: Discussionmentioning
confidence: 99%
“…As regional and global efforts to share large spectral libraries and build spectroscopy‐based estimation services are increasing (Demattê et al., 2022; Shepherd et al., 2022), it is critical to understand when calibration transfer is necessary. Harmonizing spectral collection to be consistent with the primary instrument may avoid the need for calibration transfer but given the diversity in instrument types and set‐ups (Benedetti & van Egmond, 2021), it is likely that the need for calibration transfer will at least have to be tested on a case‐by‐case basis.…”
Section: Discussionmentioning
confidence: 99%
“…As moisture content will vary between samples—and thus also the moisture effects—an additional dimension is added for moist samples, making calibration work overwhelming. Despite the challenges involved, applying SSL‐based calibrations on field sampled spectra appears as the most realistic and reasonable way forward; several large SSLs are already built and under development (Dangal et al, 2019; Demattê et al, 2022). However, the challenges dealing with discrepancies between field and laboratory spectra need to be addressed.…”
Section: In‐field Soil Spectroscopymentioning
confidence: 99%
“…Te accuracies of the harmonization platform of Demattê et al [12] varied in the OC and texture predictions, as some examination cases showed good accuracies and others did not. Indeed, mathematical manipulations can contribute to relating SSLs from diferent laboratories, but it is still necessary to harmonize the initial "raw" data (nonpreprocessed refectance spectra) of the SSLs.…”
Section: Introductionmentioning
confidence: 99%
“…To harmonize the global SSL (collected from SSLs using diferent protocols), Viscarra Rossel et al [1] rectifed noise efects using wavelet transformation, following the approach of Viscarra Rossel and Lark [11] to improve the performance of spectral-based models for soil properties characterization. Te frst online spectral service was recently published by Demattê et al [12], who provided a user-friendly system for global soil spectra communication based on the BSSL and tested it with the spectra from 65 countries.…”
Section: Introductionmentioning
confidence: 99%